Education storytelling & digitization for the congregation of GKI Kwitang Bajem Cililitan, East Jakarta - Imelda Masni Juniaty Sianipar; Febrimarini Br. Sinulingga; Darynaufal Mulyaman; Audrey Gracias; Destini Natalia Situmorang; Rafael Leonardo; Novret Hiklai; Yubilliam Engthawils Aziranoth; Yehuda Parningotan Manullang; Devanove Ray (Privietlab, 2026)
This community engagement program focuses on improving storytelling competence and basic digital literacy among Sunday School teachers and youth at GKI Kwitang Bajem Cililitan, East Jakarta. The program was implemented through interdisciplinary collaboration between the Faculty of Social and Political Sciences and the Faculty of Letters and Languages, integrating social communication perspectives with literary and creative approaches. The main challenges identified were limited creative storytelling techniques and insufficient technical skills in using digital presentation media to support worship and educational activities. The methods applied included participatory training, hands-on workshops, storytelling simulations using puppet stages, and basic PowerPoint operation training for worship presentations. Program implementation emphasized practical skill development through guided practice and direct evaluation. The results show that participants were able to deliver stories more effectively, demonstrate improved narrative confidence, and operate presentation media with greater accuracy during church services. Audience engagement during Sunday School sessions also increased as storytelling became more interactive and visually supported. In conclusion, the integration of storytelling training and basic digital literacy proved effective in enhancing communication skills and youth participation within a faith-based community. This program contributes to sustainable community empowerment by strengthening creative expression and technical support for religious and educational activities.